PERANCANGAN MEDIA EDUKASI DAMPAK POLA ASUH OTORITER BERBASIS SOSIAL MEDIA: DESIGNING EDUCATIONAL MEDIA ON THE IMPACT OF AUTHORITARIAN PARENTING BASED ON SOCIAL MEDIA - Yassinta Fitria; Pungky Febi Arifianto; Aninditya Daniar (Jurnal Dimensi Seni Rupa dan Desain, 2025)
Authoritarian parenting is one of the parenting approaches characterized by high levels of control and one-way communication, which can negatively affect a child's emotional and social development. This study is motivated by the issues arising from the implementation of authoritarian parenting, as this approach can significantly influence children's character development, particularly in an era of rapid technological advancement. The lack of public understanding regarding the impact of this parenting style highlights the need for the design of educational media that is informative and easily accessible, especially for millennial parents. This research aims to design educational media on authoritarian parenting by utilizing social media platforms. The design output consists of visual and narrative content. Through an engaging and innovative visual communication design approach, the media is expected to provide valuable insights for parents regarding authoritarian parenting in order to support the optimal development of children.